2018
DOI: 10.1177/0333102418764895
|View full text |Cite
|
Sign up to set email alerts
|

Hemicrania continua: Case series presenting in an orofacial pain clinic

Abstract: Comorbid pain conditions can be expected in patients with HC presenting to orofacial pain clinics. Symptom presentation varies, and multimodal treatment approach is necessary for success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Traditionally, HC has been considered a rare condition and a recent study by Hryvenko and colleagues reviewed 1617 new patients seen in their TMD and Orofacial Pain Clinic, and only found 6 (0.4%) patients with HC, with 5 patients with nearly complete response with oral indomethacin (150-225 mg/day) and one patient had to remain on 75 mg/day due to intolerable side effects, and therefore had partial pain relief [21]. In a pooled analysis of published HC case series, HC represents 1.7% (range 1.3–2.3%) of neurology or headache clinics patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, HC has been considered a rare condition and a recent study by Hryvenko and colleagues reviewed 1617 new patients seen in their TMD and Orofacial Pain Clinic, and only found 6 (0.4%) patients with HC, with 5 patients with nearly complete response with oral indomethacin (150-225 mg/day) and one patient had to remain on 75 mg/day due to intolerable side effects, and therefore had partial pain relief [21]. In a pooled analysis of published HC case series, HC represents 1.7% (range 1.3–2.3%) of neurology or headache clinics patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…The literature search for HC yielded 48 records. Ten studies [13,17,[22][23][24][25][26][27][28][29] with a total of 131 patients were included in the pooled analyses.…”
Section: Methodsmentioning
confidence: 99%
“…In the second series, the mean effective dose was 78 mg [17]. Pooled analysis of four studies [17,24,26,27] with a total of 82 participants showed a responder proportion of 1.0 (95% CI 0.98 to 1.00). After achieving headache relief, it is often advisable to find the lowest maintenance dose [17,27].…”
Section: Preventative Treatmentmentioning
confidence: 96%
“…Hemicrania continua is a rare entity, found between 1.3 and 2.3% of all patients seen in headache clinics (1,6,7). Its incidence on the general population is di cult to estimate due to the lack of reported case or cases that go underdiagnosed(8).…”
Section: Introductionmentioning
confidence: 99%